Seasonal dynamics of Pollinating insects in Majuli, Assam - Pollobi Duara (The Bioscan, 2026)
Pollinating insects play a crucial role in maintaining biodiversity by facilitating plant reproduction. Their diversity and abundance differ considerably across various seasons. The objective of this study was to study the seasonal dynamics of pollinating insects. Direct observation and visual count methods were used monthly throughout the year at pre-monsoon (March to may), monsoon (June to September), post-monsoon (October-November), and winter (November to February). Quantitative data on flower density, diversity and phenology were recorded. The population of pollinating insects often follow a seasonal pattern. Their abundance increases during spring and early summer and directly proportional to floral abundance. Conditions such as heavy monsoon or dry winters also effect pollinator diversity. Phenology of flower also influence foraging behaviour. Seasonal dynamics of pollinating insects are closely linked to floral phenology and environmental conditions. Keywords Biodiversity, Pollinating insects, Flower phenology, Seasonal dynamics.